Takeaways from the special issue on the practice of replication - W. Robert Reed (Kiel Institute for the World Economy (IfW), 2019)
In July 2017, issued a call for papers for a special issue on "The Practice of Replication." In that call, the journal explained that there was no generally accepted procedure for how to do a replication. Likewise, there was no generally accepted standard for determining whether a replication "confirms" or "disconfirms" an original study. Accordingly, the journal called for papers to identify principles for how to do a replication and how to interpret its results; and to apply those principles in crafting a replication plan for a study of the author's choosing. The hope was that this exercise would produce some progress on "the practice of replication". The special issue is now complete with a total of eight journal articles. This commentary places the respective articles within a common framework and identifies observations and lessons learned from the respective studies.
Keywords: C10; C18; C50; 330; replication; pre-analysis plan; reproduction; repetition; extension; robustness